Do the combination models perform better than the fundamental models in forecasting the exchange rates? - Liu, Harn Jy (2020)
This study examines the predictability of the simple average combination model and the inverse average error combination model in forecasting the out-of-sample EUR/USD, GBP/USD, and JPY/USD exchange rates from 1st July 2019 to 30th June 2020. Out of the three currency pairs examined, both of the combination models only show evidence in forecasting the JPY/USD exchange rate under the 1-month horizon, in which the absolute values of their z-statistics are smaller than the two-tailed 5% significance level critical value, 1.96.